Nota sobre encontro de Phlebotominae (Diptera: Psychodidae) no litoral sul do Estado de São Paulo, Brasil Note on the finding of Phlebotominae (Diptera: Psychodidae) on the Southern part of the coast of State of S. Paulo, Brazil - Almério de Castro Gomes; Eunice Aparecida Bianchi Galati; Carmen Moreno Classer (Universidade de São Paulo, 1990)
Durante as realizações de dois estudos sobre mosquito Culicidae, empregando-se armadilhas luminosas tipo CDC e Shanon, além de isca humana, foram capturados cinco espécies de Phlebotominae, entre as quais se encontravam Lutzomyia intermedia e L. flaviscutellata. As localidades investigadas eram alagadiças e raros casos humanos de leishmaniose tegumentar foram registrados entre os moradores locais. As duas situações sugerem ser estes casos autóctones. Five species of phlebotomine sandflies were cought on the Southern part of the coast of S. Paulo, Brazil. CDC-light and Shannon traps were used, as well as human-bait, during two investigations into Culicidae moquitoes. Lutzomyia intermedia and L. flaviscutellata were found among those sandflies. The locaties investigated were swampy environments and scant human cases of cutaneous leishmaniasis have been notified there. Both situations suggest the autochthonous nature of the human cases registered there.